Keberlanjutan Perbankan Islam dalam Sistem Perbankan Ganda: Analisis Kerangka Regulasi, Stabilitas Keuangan, dan Kapasitas Kelembagaan - Zainul Arif (Journal of Economic and Business Advancement, 2026)
This study examines the sustainability of Islamic banking within a dual banking system by evaluating the interaction between regulatory frameworks, financial stability dynamics, and institutional capacity in the development of the Islamic financial industry. The research adopts a non-empirical approach using normative–analytical methods supported by secondary financial data analysis to assess the effectiveness of legal and institutional structures governing Islamic banking. The findings indicate that the regulatory framework provides a formal legal foundation for Islamic banking operations, yet structural asymmetries in market share and institutional capacity continue to influence its competitive position. The study highlights that the long-term viability of Islamic banking depends on coherent regulatory policies, strengthened institutional governance, and strategic integration within the national financial system.